2020
DOI: 10.1111/imcb.12394
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism of Leishmania granulomas

Abstract: Leishmania are parasitic protists that cause a spectrum of diseases in humans characterized by the formation of granulomatous lesions in the skin or other tissues, such as liver and spleen. The extent to which Leishmania granulomas constrain or promote parasite growth is critically dependent on the host Thelper type 1/T-helper type 2 immune response and the localized functional polarization of infected and noninfected macrophages toward a classically (M1) or alternatively (M2) activated phenotype. Recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 85 publications
(227 reference statements)
0
42
0
Order By: Relevance
“…Thus, skin parasite patches may represent areas of where amastigotes are proliferative, while inter-patch space could mark areas of dormant amastigotes. Whether host cell metabolism stimulates / supports amastigotes to proliferate in the mammalian host skin 33 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, skin parasite patches may represent areas of where amastigotes are proliferative, while inter-patch space could mark areas of dormant amastigotes. Whether host cell metabolism stimulates / supports amastigotes to proliferate in the mammalian host skin 33 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that macrophage work as antigenpresenting cells to uptake, process and present parasitic antigens, initiating and inducing adaptive immune response. Macrophage can be divided into M1 and M2 types, exhibiting distinguished metabolic characteristics (27). M1 macrophage is shown to increase the expression of glycolysis and pentose phosphate pathways, while M2 macrophage is induced after the stimulation of IL-4 and maintains mitochondrial respiration and OXPHOS (Reviewed by Reference 7).…”
Section: Macrophage Helminth Parasite Infections Induce M2 Macrophagementioning
confidence: 99%
“…Emerging evidence has indicated that parasites or their derived molecules can reprogram the metabolic events in macrophage, DC, T and B cells of host, thereby modulating the anti-infective immunity and creating a promised or moderate pathophysiological state for the growth and development of parasites. However, only sporadic mechanistic investigations in the view of immunometabolism have been reported (27,38). Several metabolites may be implicated in the underlying mechanism of parasitic infection and immunity.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…A hallmark of all Leishmania infections is the formation of inflammatory lesions or granulomas, comprising large aggregates of infected and uninfected macrophages and other immune cells (10,(16)(17)(18). Granulomas generally arise at or near the site of the sandfly bite or can occur in distal tissues, including the liver and spleen in the case of viscerotropic species (16,19).…”
mentioning
confidence: 99%
“…primarily infect macrophages and monocytes in developing granulomas, proliferating as amastigote stages within a vacuolar compartment that contains all the markers of a mature phagolysosome (22). Although Leishmania granulomas generally lack a caseous core and have a more homogeneous structure than granulomas induced by other pathogens, such as Mycobacteria tuberculosis (23), substantial microheterogeneity is likely to occur within these tissues due to variability in the origin and activation state of macrophages and monocytes (18). For example, the development of a dominant CD4 1 -dependent Thelper 1 cells (TH1) host immune response, with local production of interleukin-12 (IL-12), gamma interferon, and tumor necrosis factor alpha, can lead to polarization of granuloma monocytes/macrophages toward a proinflammatory M1 phenotype, with increased expression of iNOS and production of nitrous oxide (NO) and concomitant restriction of parasite growth (20,24).…”
mentioning
confidence: 99%